(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Collaborative care models are essential in modern healthcare for optimizing patient outcomes and safety. This paper examines the key components and benefits of collaborative care models, emphasizing the importance of interdisciplinary teamwork, communication, and shared decision-making.